"Metallophilic crosslinking" to provide fast‐curing and mendable poly(urethane‐metallothiolate) elastomers. Issue 9 (3rd February 2015) - Ruiz de Luzuriaga, Alaitz; Rekondo, Alaitz; Martin, Roberto; Cabañero, Germán; Grande, Hans J.; Odriozola, Ibon
Abstract : Thiol‐functionalized liquid polyurethane is reacted with silver ions to obtain a supramolecular network stabilized by Ag–Ag metallophilic attractions.